Key Factors for Online Branding Success in India: An ISM Approach - Kaur , Mandeep (Asian Journal of Engineering and Applied Technology, 2020)
In today’s digital age it is essential to analyse the factors that influence the success of online branding. Pure play e-tailer, Brick and mortar, click and mortar companies are required to follow online branding strategy. As online branding is the need of the hour companies are moving on the track where the ultimate destination is to adopt online branding as the strategy to stay ahead. Online branding is moving at the pace of the light. To keep up, companies need a robust foundation with the judgment to think precariously about the critical success factors for online branding. The purpose of the paper is to identify factors that influence the success of online branding, interrelationship among those factors and categories them in line with its driving and dependence power. These factors will help to prepare the model for companies who are planning to go for online branding strategy. Interpretative Structural Modelling approach is used to construct this model. The result found that both online factors and offline factors influence the success of online branding. Future research may endeavour to statistically validate the proposed model and may also expand the model by suggesting other factors that are influencing the success of online branding. Little research has investigated the interrelationship among factors which are affecting the success of online branding and thereby inducing companies to go for online branding. In addition the present paper contributed insights developed from the model that would help companies in taking decision related to online branding.